Performance Profile of Teachers at SMA Negeri 1 Lubai Ulu (Peer Assessment of Teachers' Performance at SMA Negeri 1 Lubai Ulu) - Hastiana, Yetty; Rohmah, Siti (Graduate Program Magister Manajemen Pendidikan, 2023)
This research aims to determine the performance of teachers at SMA Negeri 1 Lubai Ulu, Lubai Ulu District, Muara Enim Regency based on peer assessment. This study uses qualitative research with a qualitative descriptive approach. The study was conducted at SMA Negeri 1 Lubai Ulu, Lubai Ulu District, Muara Enim Regency. The techniques used in collecting data are interviews, observations, and documentation. The data analysis in this study includes data reduction, data presentation, and drawing conclusions. The validity of the data is ensured through credibility, transferability, dependability, and confirmability. The assessment is based on the daily behavior of teachers, their relationships with peers, and their professional conduct. The assessment is not only based on peer assessment instruments but also supported by interviews, checking learning materials, and observing/supervising each teacher in the classroom. The results of the performance assessment of teachers by the researcher as peers show that, in general, the performance of teachers is good. However, with the changes in the curriculum, teachers need guidance and mentoring to be able to perform their duties in accordance with the process standards specified in the Minister of Education and Culture Regulation 65/2013, Minister of Education and Culture Ristek No.16/2022, and Minister of Education and Culture Regulation 57/2014, which mandate that teachers must implement scientific-based learning and authentic assessment for the 2013 curriculum and differentiated learning with a Technological Pedagogical Content Knowledge (TPACK) approach. Some aspects of the assessment are still lacking in some teachers and can be used as evaluation and self-reflection for the school and the teachers concerned.